Chalcone as a versatile scaffold: An overview - Saba, Farooq; Zainab, Ngaini (Elsevier Inc., 2026)
Chalcone is a stable organic compound with an aromatic ring structure and α, β-unsaturated carbonyl moiety. It has a wide spectrum of bioactivities, including anti-HIV, antimicrobial, anticancer, antivirus, antitubercular, antioxidant, and antidiabetes properties. Chalcone derivatives are easily synthesized and have numerous applications in the pharmaceutical industry, liquid crystal sectors, dye-sensitized solar cell sectors, agricultural, cosmetic properties, corrosion inhibition, and many others. Chalcone can be synthesized in many ways, and researchers have been particularly interested in the Claisen–Schmidt condensation process because of its simple conditions and stable reactants. This chapter will cover a brief history of chalcone and its structural features, synthesis, and structural activity relationship of chalcones as active scaffolds for heterocyclic compounds with economical, eco-friendly, effective, and high-yield strategies.